Paper-based sensor for water-soluble gases detection - Chong, Esther Yee Xin (2023)
In this work, an inexpensive and environmentally friendly colorimetric paperbased sensor for rapid detection of water-soluble gases is fabricated. The detection principle is based on colour change upon exposure to water-soluble gases to anthocyanin-containing filter paper, which can be observed by the naked eye. The paper-based sensor is fabricated from red cabbage powder, ethanol, deionized water, filter paper, and different concentrations of polyvinyl alcohol (PVA). The colour change of the sensor is characterised by a UVVisible Spectrophotometer (UV-Vis), a colorimeter, and an optical microchip sensor (SparkFun MAX30105). The paper-based sensor shows colour changes from reddish-purple to pink upon exposure to acidic gas (pH 0-1) and reddishpurple to green upon exposure to acidic gas (pH 11–13). The highest total colour change ΔE, peak shift, and recovery time are 65.8872, 55 nm, and 4.11 minutes, respectively, exhibited by a paper-based sensor with 20 mg/ml PVA when exposed to 15 ppm alkaline gas. The paper-based sensor also recovered its colour as it is exposed to ambient air. These results indicate that a paper-based sensor that contains 20 mg/ml PVA is a good indicator for water-soluble gases, and it is reusable.